2018
DOI: 10.1097/sih.0000000000000335
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-Based Education to Train Learners to “Speak Up” in the Clinical Environment

Abstract: Introduction Assertiveness is essential for communication and/or speaking up. We performed a randomized trial to assess the effectiveness of assertiveness/advocacy/CUS/two-challenge rule (AACT) simulation-based education for labor and delivery, as well as postpartum nurses. We aimed to determine whether this training would improve labor and delivery and postpartum nurses speaking up in the clinical setting. Methods We conducted a randomized controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 27 publications
0
25
0
2
Order By: Relevance
“…The searches yielded 1712 unique records of which 1505 were excluded during title and abstract review. Following full text review of the remaining 207 papers, 187 were excluded based on reasons listed in Fig 1. Ultimately, the search yielded 20 papers [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] reporting on 19 studies. One study was reported in two papers [49,50].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The searches yielded 1712 unique records of which 1505 were excluded during title and abstract review. Following full text review of the remaining 207 papers, 187 were excluded based on reasons listed in Fig 1. Ultimately, the search yielded 20 papers [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] reporting on 19 studies. One study was reported in two papers [49,50].…”
Section: Resultsmentioning
confidence: 99%
“…The retained studies were published between 2009 and 2020 (see Table 1). Studies were conducted in Australia [39], Belgium [55], France [56], Germany [40,57], New Zealand [41], United States [42][43][44][45][46][47][48][49][50][51][52]54], Singapore [58], and Taiwan [53]. Key study characteristics are presented in Table 1 and outlined below.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations